2015
DOI: 10.1590/s0036-46652015000300012
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR IDENTIFICATION AND ANTIMICROBIAL RESISTANCE PATTERN OF SEVEN CLINICAL ISOLATES OF Nocardia spp. IN BRAZIL

Abstract: Nocardia is a ubiquitous microorganism related to pyogranulomatous infection, which is difficult to treat in humans and animals. The occurrence of the disease is on the rise in many countries due to an increase in immunosuppressive diseases and treatments. This report of cases from Brazil presents the genotypic characterization and the antimicrobial susceptibility pattern using the disk-diffusion method and inhibitory minimal concentration with E-test® strips. In summary, this report focuses on infections in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
1
11
0
6
Order By: Relevance
“…Our study showed that most of the isolates (94%) were susceptible to Trimethoprim-sulphamethoxazole which is in agreement with several other studies done on aerobic Actinomycetes[12] [19][20]. However, resistance to Trimethoprim-sulphamethoxazole has been observed in different studies[11] [14] [15][17] [18][21] among others. This is on the contrary to the current study.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed that most of the isolates (94%) were susceptible to Trimethoprim-sulphamethoxazole which is in agreement with several other studies done on aerobic Actinomycetes[12] [19][20]. However, resistance to Trimethoprim-sulphamethoxazole has been observed in different studies[11] [14] [15][17] [18][21] among others. This is on the contrary to the current study.…”
supporting
confidence: 91%
“…Antimicrobial susceptibility testing of aerobic Actinomycetes isolated from clinical specimens is very important as it can help in guiding the therapy for infections. Actinomycetes are slow growing and most of them clumps and aggregates hence causing difficulty in carrying out the antimicrobial susceptibility testing [11] [12]. Broth microdilution method was used to perform the AST which is the approved standard method by CLSI for antimicrobial susceptibility testing of Actinomycetes [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sulfonamida é o agente mais recomendado, porém, em pacientes com doenças sistêmicas, a taxa de mortalidade com esse antibiótico isoladamente é alta. Espécies diferentes de Nocardia apresentam susceptibilidades diferentes aos antimicrobianos, sendo necessário o uso inicial de dois ou três agentes terapêuticos (Condas et al, 2015). No paciente relatado, a multiterapia antibacteriana foi instituída precocemente, porém não obteve sucesso terapêutico.…”
Section: Discussionunclassified
“…In Brazil, pulmonary disease is the most common nocardiosis [ 7 ]. N. farcinica and N. asiatica have been isolated from rare cases of primary cutaneous nocardiosis in Brazil [ 8 ]. Cutaneous involvement may develop as one of four types: superficial skin infection, mycetoma, lymphocutaneous infection, or systemic disease with cutaneous involvement [ 1 ].…”
Section: Discussionmentioning
confidence: 99%